Smart E-Skin Cancer Care in Europe During and After the COVID-19 Pandemic: A Multidisciplinary Expert Consensus - Malvehy, Josep; Dreno, Brigitte; Barba, Enric; Dirschka, Thomas; Fumero, Emilio; Greis , Christian; Gupta, Girish; Lacarrubba , Francesco; Micali , Giuseppe; Moreno, David; Pellacani, Giovanni; Sampietro-Colom, Laura; et al. (Dermatology Practical & Conceptual, 2023)
Introduction: Melanoma is the deadliest of all the skin cancers and its incidence is increasing every year in Europe. Patients with melanoma often present late to the specialist and treatment is delayed for many reasons (delay in patient consultation, misdiagnosis by general practitioners, and/or limited access to dermatologists). Beyond this, there are significant inequalities in skin cancer between population groups within the same country and between countries across Europe. The emergence of the COVID-19 pandemic only aggravated these health deficiencies.Objectives: The aim was to create an expert opinion about the challenges in skin cancer management in Europe during the post COVID-19 acute pandemic and to identify and discuss the implementation of new technologies (including e-health and artificial intelligence defined as "Smart Skin Cancer Care") to overcome them.Methods: For this purpose, an ad-hoc questionnaire with items addressing topics of skin cancer care was developed, answered independently and discussed by a multidisciplinary European panel of experts comprising dermatologists, dermato-oncologists, patient advocacy representatives, digital health technology experts, and health technology assessment experts.Results: After all panel of experts discussions, a multidisciplinary expert opinion was created.Conclusions: As a conclusion, the access to dermatologists is difficult and will be aggravated in the near future. This fact, together with important differences in Skin Cancer Care in Europe, suggest the need of a new approach to skin health, prevention and disease management paradigm (focused on integration of new technologies) to minimize the impact of skin cancer and to ensure optimal quality and equity.